Outside Front Cover: Volume 2 Issue 4. (22nd December 2021) - Zheng, Guangchao; Pastoriza‐Santos, Isabel; Pérez‐Juste, Jorge; Liz‐Marzán, Luis M.
Abstract : Outside front cover image : Plasmonic effects in nanomaterials, metal nanoparticles in particular, have been applied in a variety of fields, such as plasmon‐enhanced spectroscopies (e.g. surface‐enhanced Raman scattering, surface‐enhanced fluorescence, plasmon‐enhanced optical activity…), photocatalysis, cancer therapy, etc. The performance of plasmonic nanometals can be further enhanced by combining them with metal‐organic frameworks (MOFs), which feature well‐defined pore size, large surface‐area, diverse chemical/physical information, and efficient capture of specific molecules. The resulting hybrid nanomaterials, known as plasmonic MOFs, offer improved and further extended applications through a synergistic activity. Application‐oriented topologies and compositions of plasmonic MOFs can be precisely controlled by means of thermodynamic and kinetic parameters during the synthetic process. (DOI: https://doi.org/10.1002/smm2.1047 )